2020
DOI: 10.18632/aging.102882
|View full text |Cite
|
Sign up to set email alerts
|

Sirt1 antisense long non-coding RNA attenuates pulmonary fibrosis through sirt1-mediated epithelial-mesenchymal transition

Abstract: Long noncoding RNAs sirt1 antisense (sirt1 AS) was reported to play crucial roles in the progression of organ fibrosis. However, the roles of sirt1 AS in idiopathic pulmonary fibrosis (IPF) are still unknown. In addition, we have previously demonstrated that astragaloside IV (ASV), a bioactive saponin extract of the Astragalus root, significantly alleviates IPF by inhibiting transforming growth factor β1 (TGF-β1) induced epithelial-mesenchymal transition (EMT). Further investigations into the influence of ASV … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 38 publications
0
28
0
Order By: Relevance
“…This is in stark contrast to our finding. However, research on EMT in pulmonary fibrosis has been still reported in the lots of literatures recently [61][62][63][64][65][66] . There is no conclusion in this field.…”
Section: Discussionmentioning
confidence: 99%
“…This is in stark contrast to our finding. However, research on EMT in pulmonary fibrosis has been still reported in the lots of literatures recently [61][62][63][64][65][66] . There is no conclusion in this field.…”
Section: Discussionmentioning
confidence: 99%
“…SIRT-AS protects SIRT1 mRNA degradation by inhibiting miR-34a binding to the 3′UTR of SIRT1 ( 162 ). In one study of bleomycin-induced lung fibrosis, SIRT1-AS overexpression inhibited TGF-β-mediated EMT ( 163 ). Despite these data, more studies will be necessary to confirm the roles of ANRIL and SIRT1-AS in COPD and pulmonary fibrosis.…”
Section: Non-coding Rnas In Aging Ipf and Copdmentioning
confidence: 99%
“…Long non‐coding RNAs (lncRNAs) are a class of non‐coding transcripts that are longer than 200 nucleotides, lacking protein‐coding capacity (Qian, Cai, & Qian, 2020). A large amount of studies have demonstrated that lncRNAs are widely involved in various biologic processes such as epigenetic regulation, cell proliferation, apoptosis, and differentiation (Haemmerle & Gutschner, 2015).…”
Section: Introductionmentioning
confidence: 99%